2002
DOI: 10.1007/bf03000104
|View full text |Cite
|
Sign up to set email alerts
|

Correction of nonuniform attenuation and image fusion in SPECT imaging by means of separate X-ray CT

Abstract: Improvements in image quality and quantitation measurement, and the addition of detailed anatomical structures are important topics for single-photon emission tomography (SPECT). The goal of this study was to develop a practical system enabling both nonuniform attenuation correction and image fusion of SPECT images by means of high-performance X-ray computed tomography (CT). A SPECT system and a helical X-ray CT system were placed next to each other and linked with Ethernet. To avoid positional differences bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 6 publications
0
23
0
2
Order By: Relevance
“…Using the software on the image data processor, AC of original 128 9 128 matrix DIBrH perfusion SPECT at each lung section was automatically performed based upon 168 9 168 matrix co-registered CT-derived attenuation coefficient maps with the calibration curve for 99m Tc according to the previous studies [3,5,7,8,11]. These attenuation coefficient maps were created from the data of variable-effective linear-attenuation coefficient values calculated from spatially corrected CT data: attenuation coefficient = 0.…”
Section: Ac Of Dibrh Perfusion Spectmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the software on the image data processor, AC of original 128 9 128 matrix DIBrH perfusion SPECT at each lung section was automatically performed based upon 168 9 168 matrix co-registered CT-derived attenuation coefficient maps with the calibration curve for 99m Tc according to the previous studies [3,5,7,8,11]. These attenuation coefficient maps were created from the data of variable-effective linear-attenuation coefficient values calculated from spatially corrected CT data: attenuation coefficient = 0.…”
Section: Ac Of Dibrh Perfusion Spectmentioning
confidence: 99%
“…Since photon interaction is significant and complicated in the thorax with variable photon attenuation structures such as chest wall, vertebrae and lungs [1][2][3][4][5][6][7][8][9][10][11][12], non-uniform photon attenuation correction (AC) is indispensable for better assessment of lung perfusion on perfusion SPECT. The use of thoracic transmission computed tomography (TCT) obtained by radioactive external sources is one of the options for non-uniform AC of perfusion SPECT, but it has not been widely used for clinical practice, because of complicated procedure and unavailability of radioactive external sources in some SPECT systems [1,2,4,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A SPECT/PET system using 99m Tc-GSA (Forte; Philips/ADAC Laboratories, Milpitas, CA, USA) was used in the study, as reported previously [20, 27]. The details of our protocol were written in the previous paper [20].…”
Section: Methodsmentioning
confidence: 99%
“…High spatial and temporal resolution is necessary for the use of a multi-compartment model since the input function can only be determined from the portal vein and liver artery in this way. A further disadvantage of nuclear medicine techniques is the necessary and complicated attenuation correction and the resulting signal inhomogeneity [82]. An advantage of nuclear medicine techniques is the lack of a background signal.…”
mentioning
confidence: 99%